Not-so-innocent bystanders: Trade with neighbors of sanctioned countries - Daria Suprunenko (Osnabrück University, Institute of Empirical Economic Research, 2024)
Geographic neighbors of sanctioned countries (targets) may suffer from indirect effects of sanctions or benefit by helping targets circumvent restrictions. I study the effects of sanctions on trade among neighbors and targets using data from BACI for 2002-2022 and separately accounting for export of sensitive goods: arms, dual use goods and machinery. I find that export of dual use goods (in value) and machinery (in value and weight) from benevolent neighbors to targets increases when sanctions are in place. Additionally, I show that the weight of arms exported by neighbors to Iran, as well as value of dual use goods and weight of machinery exported to Russia were significantly higher with sanctions in place suggesting that their neighbors were not innocent bystanders.
Keywords: F13; F51; 330; Trade sanctions; extraterritorial effects; trade